(untitled) (World Bulletin of Social Sciences, 2025)
This study explores the structural and functional dimensions of code-switching in Uzbek-Russian bilingual speech, focusing on informal spoken interactions as a rich site of linguistic and sociocultural meaning-making. Situated within the frameworks of sociolinguistics, discourse analysis, and bilingualism studies, the research draws on Poplack’s structural typology and functional models proposed by Gumperz, Appel and Muysken. The analysis is based on a corpus of naturally occurring utterances from urban Uzbek-Russian bilinguals, revealing code-switching as a patterned and purposeful practice rather than a random or deficient use of language. Findings show that intrasentential switching is the most frequent type, particularly among younger and more proficient bilinguals, allowing for fluid integration of lexical and syntactic elements from both languages. Inter-sentential switching often serves rhetorical and discursive functions such as emphasis or thematic boundary marking, while tag-switching is employed to facilitate pragmatic alignment, soften speech acts, or manage interpersonal dynamics. Ultimately, the paper argues that code-switching in the Uzbek-Russian context reflects broader sociolinguistic realities shaped by post-Soviet language ideologies, educational backgrounds, and evolving identity formations. Far from being a linguistic anomaly, it is a sophisticated strategy through which speakers negotiate meaning, assert belonging, and navigate multiple social registers. Code-switching thus emerges as a central practice in the bilingual repertoire of Uzbek-Russian speakers, illustrating the dynamic interplay between language, culture, and identity.